Biallelic HERC1 mutations in a syndromic form of overgrowth and intellectual disability (2015)
We report two Colombian siblings affected by overgrowth, intellectual disability and facial dysmorphism. Exome (via NGS) and Sanger sequencing revealed that biallelic sequence variants in a novel gene (HERC1) might be related to the disease pathogenesis. These results provide useful data for future genotype-phenotype correlations and for a molecular diagnosis of overgrowth. © 2015 John Wiley and Sons A/S. Published by John Wiley and Sons Ltd.